Advanced Placement® Human Geography: Looking Back and Looking Ahead. Issue 3 (3rd May 2016) - Lanegran, David A.; Zeigler, Donald J.
ABSTRACT: Over the past fifteen years, AP Human Geography has grown in numbers and spread to almost every state. This article synopsizes the early history of the subject, summarizes the course and the exam, highlights positive impacts on the discipline of geography, and focuses on the following three issues: teachers who come to the course having majored in other subjects, the large numbers of students taking the exam as ninth graders, and the need to incorporate more geospatial technologies and critical geography into the course outline.